A STUDY OF LEFT ATRIAL APPENDAGE FLOW BY DOPPLERTRANSESOPHAGEAL ECHOCARDIOGRAPHY IN PATIENTS WITHATRIAL SEPTAL DEFECT - Funjan, Mawada Mousa (Al-Nahrain Journal of Science, 2009)
Transesophageal echocardiography TEE is performed in subjects with atrial septal defect (ASD) to define the characteristics of left atrial appendage (LAA) blood flow pattern.Normally, LAA flow velocity pattern is primarily determined by the left heart performance. We hypothesized that the impact of left – side heart dynamics on LAA flow velocity pattern is diminished in patients with ASD because of the presence of a left –to-right shunt into the low-resistance right side of the heart.Methods:Transesophageal echocardiography was performed in 29 adults with a large uncomplicated secundum ASD. Maximum defect diameter varied from 1.40 - to -3.9 cm, mean (2.37 ±0.79) cm. All patients were in normal sinus rhythm. Results: In 29 subjects the LAA flow velocity pattern lacked distinct early diastolic LAA outflow wave. Instead, we notice that the early diastolic LAA outflow and LAA contraction waves in late diastolic contraction tend to merge followed by a slightly higher emptying velocity (early systolic velocity).Conclusion:The pattern of flow velocity of left atrial appendage by spectral pulsed Doppler echocardiography affected by ASD hemodynamics.